Respuesta :

Answer:

x=9 is wrong -27/3=-9

-/+= -

Step-by-step explanation:

5x-8x+9=-6(x+3)

-3x+9=-6x-18

-3x+6x=-18-9

3x=-27

x=-27/3

x=-9

The correct answer is: X = -9

1. Combine like terms (5x - 8x

  • 5 - 8 = (-3)

-3x + 9 = -6(x + 3)

2. Expand -6(x + 3)

Use distributive property. a(b + c) = ab + ac

A = (-6), B = X, C = 3

= -6x + (-6) · 3

Apply the minus and/or plus rules.

+ (-a) = -a

= -6x - 6 · 3

Multiply 6 and 3.

6 · 3 = 18.

-3x + 9 = -6 = 18

3. Subtract from both sides.

  • -3x + 9(-9)  = -6 = 18 (-9)

-3x = -6x - 9

4. Simplify.

  • -3x = -6x - 9 (×3)

-3x = -6x - 27

5. Add 6x to both sides.

  • -3x = -6x - 27 + 6x

3x = -27

6. Divide both sides by 3.

3x ÷ 3 = -27 ÷ 3

-27 ÷ 3 = -9

Answer: X = (-9)